Atipamezole, a specific α2A antagonist, suppresses spike‐and‐wave discharges and alters Ca2⁺/calmodulin‐dependent protein kinase II in the thalamus of genetic absence epilepsy rats. (23rd October 2020) - Yavuz, Melis; Aydın, Banu; Çarçak, Nihan; Akman, Özlem; Raci Yananlı, Hasan; Onat, Filiz
Abstract: Objective: The role of α2A adrenergic receptors (α2A ARs) in absence epilepsy is not well characterized. Therefore, we investigated the outcomes of the specific antagonism of α2A ARs on the spike‐and‐wave discharges (SWDs) in genetic absence epilepsy rats from Strasbourg (GAERSs), together with its influence on the behavior and second messenger systems, which may point to the mechanisms to which a possible SWD modulation can be related. Methods: Atipamezole, an α2A AR antagonist, was administered intracerebroventricularly to the adult GAERSs, and electroencephalography (EEG) was conducted. The cumulative duration and number of SWDs, and the mean duration of each SWD complex were counted. The relative power of the EEG frequency bands and behavioral activity after the acute application of two doses (12 and 31 μg/5 μL) of atipamezole were evaluated. The levels of cyclic adenosine monophosphate and calcium/calmodulin‐dependent kinase II (CaMKII) were measured in the cortex, thalamus, and hippocampus of naive Wistar rats and GAERSs, administered with artificial cerebrospinal fluid (aCSF) as a vehicle, or either acute or chronic atipamezole (12 μg), the latter being administered for 5 consecutive days. Results: Atipamezole significantly suppressed SWDs dose‐dependently, without affecting the relative power values of EEG frequency spectrum. The stereotypic activity was significantly lower in both naive Wistar rats and GAERSs receiving the highest dose (31 μg) of atipamezole compared to GAERSs receiving aCSF. In GAERSs, CaMKII levels were found to be higher in the thalamus after the acute and chronic application of SWD‐suppressing doses of atipamezole (12 and 31 μg) compared to aCSF. Significance: This study emphasizes the α2 AR‐related modulation of absence epilepsy and particularly the significance of α2 AR antagonism in suppressing SWDs. Atipamezole's SWD‐suppressive actions may be through CaMKII‐mediated second messenger systems in the thalamus.